Empowerment in the perioperative dialog. Issue 1 (18th August 2020) - Abelsson, Anna; Falk, Peter; Sundberg, Bengt; Nygårdh, Annette
Abstract: Aim: To describe how the nurse anaesthetist empowers the patient in the perioperative dialogue. Design: A qualitative descriptive design with interviews with 12 nurse anaesthetist (NA). Method: A hermeneutic text interpretation with a foundation in Gibson's empowerment model. Result: The results highlight Gibson's nursing domain: Helper, Supporter, Counsellor, Educator, Resource Consultant, Resource Mobilizer, Facilitator, Enabler and Advocate. The overall understanding is revealed as a relationship can be built through closeness between the patient and the NA. The NA helps the patient master the situation by talking to and touching the patient. The patient is helped to find their own strengths and to cope with their fears. The patients decide over their own bodies. When the patients do not want to or cope with protecting themselves, the NA protects and represents the patient.